Arkeologi Islam Nusantara: Kebudayaan Materi untuk Kehidupan Masa Kini dan Masa Nanti - Akbar, Ali (Faculty of Islam Nusantara, Nahdlatul Ulama University of Indonesia (Unusia) Jakarta., 2022)
Archeology is a science that continues to develop, including the development of more specialized studies such as the Archeology of Islam Nusantara. This paper describes the word and word combinations, namely Archeology, Islam, Nusantara, and Islam Nusantara, and Archeology of Islam Nusantara. As part of archeology, the Archeology of Islam Nusantara also uses objects or data, purposes, and benefits, archaeological theories, and methods. This paper raises issues regarding objects or data, objectives, and benefits, theories and methods specifically used for Archeology of Islam Nusantara. Archeology in its latest development is not only studying objects of the past but also including present day of material culture. With these developments, it is possible to study materials or objects for the benefit of the present and the future.